Protocatechuic aldehyde ameliorates high glucose-induced podocyte injury by attenuating inflammation, oxidative stress, and apoptosis via suppression of endoplasmic reticulum stress through the GSK3β/Nrf2 pathway - Wang, Yishu; Wang, Haifeng; Li, Yang (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe core pathological feature of Diabetic kidney disease is glomerular podocyte injury. A hyperglycemic milieu induces podocyte injury through the synergistic actions of multiple pathways, including oxidative stress, inflammation, and apoptosis. Protocatechuic Aldehyde (PCA), a naturally occurring phenolic acid compound, exhibits significant antioxidant activity. However, the protective effects and underlying mechanisms of PCA on podocyte function under high-glucose conditions remain incompletely elucidated.ObjectiveTo investigate the effects and mechanism of PCA on high glucose-induced podocyte inflammation, oxidative stress, and apoptotic injury.MethodsA podocyte injury model was established by treating mouse podocytes (MPC5) with high-glucose medium. Podocytes were concurrently treated with varying concentrations of Protocatechuic Aldehyde. To explore the mechanism, cells in different treatment groups were exposed to the GSK3β inhibitor TDZD-8 and the endoplasmic reticulum stress inducer Tunicamycin (TM). The levels of inflammatory cytokines and oxidative stress markers were measured using relevant assay kits. The expression of proteins associated with inflammation, oxidative stress, apoptosis, the GSK3β/Nrf2 signaling pathway, and endoplasmic reticulum stress was detected by Western blot. Apoptosis rate of podocytes was assessed using flow cytometry.ResultsHigh glucose significantly reduced MPC5 cell viability and increased lactate dehydrogenase release; these effects were significantly reversed by PCA treatment. PCA significantly reduced the secretion of inflammatory cytokines (TNF-α, IL-1β, IL-6), restored the activities of SOD and GSH-Px, decreased MDA content, and downregulated the expression of Cox-2, iNOS, Nox2, and Nox4 proteins, thereby suppressing HG-induced podocyte inflammation and oxidative stress. Furthermore, PCA upregulated Bcl-2 expression while downregulating Bax and cleaved-caspase 3 expression, effectively inhibiting HG-induced podocyte apoptosis. Mechanistically, PCA upregulated the expression of p-GSK3β and Nrf2 proteins, activating the GSK3β/Nrf2 signaling pathway. This activation was associated with downregulation of ER stress markers (CHOP, GRP78, p-PERK), indicating suppression of podocyte ER stress. Notably, the protective effects of PCA were abrogated by co-treatment with the GSK3β inhibitor TDZD-8 or the ER stress inducer TM.ConclusionPCA attenuates high glucose-induced podocyte injury, characterized by inflammation, oxidative stress, and apoptosis, suggesting that this protection involves inhibition of ER stress via activation of the GSK3β/Nrf2 signaling pathway.